Pentakostal Dan Keberagaman Indonesia: Strategi Ayah Menanamkan Nilai Keberagaman Pada Anak Di Keluarga Kaum Pentakostal - Manurung, Kosma (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2025)
Indonesia is constructed upon a foundation of diversity, and for Indonesia, this diversity is not merely a remarkable uniqueness it possesses but also a source of prosperity and excellence. However, on the other hand, this diversity can also serve as a vulnerability or even a catalyst for unrest—if not managed with precision and wisdom, it could lead to national disintegration. Therefore, the stewardship of Indonesia's diversity must be entrusted to every member of the nation, including faithful individuals within Pentecostal families. This article seeks to narrate the strategies that fathers employ in instilling and nurturing Indonesia’s diversity values within their children in Pentecostal households. By employing a qualitative descriptive method framed within the scope of literature review, this approach aims to enrich the understanding of Indonesia in the context of its diversity, strengthen the narrative of the father’s role within Pentecostal families, and clarify strategies for embedding Indonesia’s diverse fabric into the younger generation.In conclusion, the most effective strategy for a father to cultivate an appreciation for Indonesia’s diversity values within Pentecostal families is to introduce and expose the child to diversity from an early age, serve as a genuine role model, and become a personal teacher and a trusted friend-helping the child practice and internalize the values of unity in diversity.